Balancing Precision and Voice: A Qualitative Study of QuillBot’s Role in Enhancing EFL Students’ Writing Skills (Tamaddun, 2025)
This qualitative study investigates the role of the AI-powered writing assistant QuillBot in enhancing the writing skills of secondary-level English as a Foreign Language (EFL) students in Indonesia. Twenty participants engaged with QuillBot over an eight-week period during writing assignments. Data were collected through semi-structured interviews and analysis of pre- and post-intervention writing samples. The findings indicate that QuillBot contributed significantly to improvements in grammar, sentence structure, and vocabulary usage. Non-native English speakers, in particular, demonstrated notable gains in mechanical accuracy and lexical variety. However, the tool's limitations became apparent in areas requiring higher-order thinking, such as content development, coherence, and creativity. A subset of students expressed concern about over-reliance on the tool, reporting decreased confidence when writing independently and a perceived loss of personal voice in their work. Engagement was initially high but declined over time, suggesting the novelty of AI feedback may diminish without sustained pedagogical scaffolding. The study highlights the dual potential of AI writing tools to support surface-level writing improvements while risking dependence and reduced autonomy. Implications include the need for balanced instructional approaches that combine AI feedback with human guidance to preserve critical thinking and authorial identity. Recommendations for future research include longitudinal studies and hybrid models integrating teacher- and AI-mediated feedback.